Awareness of Housewives in Choosing Halal Labeled Children's Syrup Medicine - Chuzaimah Batubara; Inayatul Widad Nasution; Sakti Andiyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Currently, pediatric medicine is a very scary phenomenon, where many children are affected by acute kidney failure and the cause is children's syrup. Many parents nowadays are concerned with halal food but not with children's medicines. Even though food that is not halal has been explained in the Qur'an and Sunnah that it can damage the human body. The purpose of this study is for mothers to be more aware of the drugs their children are taking, and to pay attention to the halal label located on the package. This research is descriptive qualitative in nature. By conducting interviews with parents who have children under two years.